Seniors' recreation centers in rural India: Need of the hour - Sherin Susan Paul; Prashant Hanumanthappa Ramamurthy; Rakesh Kumar; Mathew Ashirvatham; Kamala Russel John; Rita Isaac (Wolters Kluwer Medknow Publications, 2016)
Aim: To empower and bring the underprivileged senior citizens in the rural areas to the mainstream of life through setting up of model "senior citizens' recreation centers" that can be replicated in the other parts of the country. Materials and Methods: Six senior citizens' recreation centers are run in six villages under a community health program of a leading Medical College in South India, which were started by looking into their perceived needs and in a location where organized self-help women groups (SHGs) showed willingness to take the role of caretakers. Together there are 140 members in 6 centers and the most deserving members were identified using a participatory rural appraisal (PRA) method. These centers are open for 5 days a week and the main attraction of the center has been provision of one good, wholesome, noon-meal a day, apart from several recreational activities. The members were also assessed for chronic energy deficiency (CED) and quality of life at the beginning of enrolment using body mass index (BMI) and WHO-BREF scale. Results: The attendance to these centers was nearly 90% of the enrolled beneficiaries. A statistically significant improvement was noticed in quality of life in the physical, psychological, social, and environmental domain (P < 0.05). There was also a significant increase in the average BMI after 1 year of the intervention (P < 0.05). Conclusion: Care of underprivileged senior citizens is a growing need in the rural areas and the "Recreation centers" proved to be a beneficial model that can be easily replicated.